Pengaruh Self Help Group terhadap Pengetahuan tentang Hipertensi - Suri Salmiyati (Universitas 'Aisyiyah Yogyakarta, 2018)
This research was conducted explore the effect of self help group intervention to the knowledge level of hypertention patient in Sonopakis Village Kasihan Bantul Yogyakarta. A pre experiment research using one group pre test post design was conducted. Purposive sampling techniques was selected to recruited participants. The data was analized by using Wilcoxon. The result shows that self help group model has a significant influence to increase knowledge level of patient with hypertention (p=0.000). Awareness of negative outcome of hypertention is needed.